Management of haemangioma neck using sclerosing agent- a case report - Bhadoria, S; Saxena, R; Lavania, A (Journal of College of Medical Sciences-Nepal, 2012)
Although hemangiomas are common in infancy and childhood, they are probably developmental abnormalities rather than true neoplasms. In present case we have treated a child aged 10 years with haemangioma of the right side of the Neck. After thorough investigation we posted this for intralesional infiltration of Sclerosing agent (Inj. Polidocanol 3%) in 1:3 dilution with normal saline. Approximately 2 ml Inj. Polidocanol diluted with saline was injected into the lesion. And the same procedure was repeated in three sittings after one week interval. The size and vascularity was reduced dramatically after single procedure. Patient was followed up after one and two months interval. There was no sign of any recurrence. This Procedure was chosen as it is cosmetically more acceptable, can be used for the haemangiomas at inaccessible areas where surgery is difficult, day care procedure and cost effective. Journal of College of Medical Sciences-Nepal,2012,Vol-8,No-1, 56-59 DOI: http://dx.doi.org/10.3126/jcmsn.v8i1.6828